1997
DOI: 10.1002/jhet.5570340527
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of N‐(1H‐pyrazol‐3‐yl)arylamides and 1H‐pyrazol‐3‐amines from polylithiated C(α),N‐thiosemicarbazones and C(α),N‐semicarbazones

Abstract: C(α),N‐Thiosemicarbazones or C(α),N‐semicarbazones were polylithiated with excess lithium diiso‐propylamide, and the resulting cyclized intermediates were condensed with aromatic esters to afford N‐(1H‐pyrazol‐3‐yl)arylamides. The polylithiated intermediates were also quenched with aqueous acid to give 5‐substituted, 1H‐pyrazol‐3‐amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The IR spectrum of 7b displayed the lack of nitrile and carbonyl absorption peaks and the appearance three peaks in the region 3320–3127 cm −1 because of NH 2 and NH. Also, 1 H NMR exhibited D 2 O exchangeable broad singlet signal at δ 5.62 ppm owing to four exchangeable hydrogens (NH 2 and 2NH), as reported previously . Alternatively, compounds 7a , b were prepared from coupling reaction of 5‐aminopyrazolyl phthalazine 8 , which was synthesized from the reaction of 1 with hydrazine hydrate in EtOH at reflux temperature, with diazotized aromatic amine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IR spectrum of 7b displayed the lack of nitrile and carbonyl absorption peaks and the appearance three peaks in the region 3320–3127 cm −1 because of NH 2 and NH. Also, 1 H NMR exhibited D 2 O exchangeable broad singlet signal at δ 5.62 ppm owing to four exchangeable hydrogens (NH 2 and 2NH), as reported previously . Alternatively, compounds 7a , b were prepared from coupling reaction of 5‐aminopyrazolyl phthalazine 8 , which was synthesized from the reaction of 1 with hydrazine hydrate in EtOH at reflux temperature, with diazotized aromatic amine.…”
Section: Resultsmentioning
confidence: 99%
“…Brown crystals, yield 79%, mp 255–257°C (EtOH); IR ( ν max , cm −1 ): 3320–3172 m (NH 2 and NH), 1660–1643 (C═O), 1595–1556s (C═N), 1495 (C═C); 1 H NMR (500 MHz, DMSO‐ d 6 ) δ H (ppm): 2.26 (s, 3H, CH 3 ), 5.62 (s, broad, D 2 O exchangeable, 4H, NH 2 , and 2NH, appear together) , 7.17 (d, 2H, J 8 Hz, Ar─H), 7.39 (d, 2H, J 7.5 Hz, Ar─H), 7.82 (dd, 2H, J 9.5, 3.5 Hz, phthalazine‐H), 8.06 (dd, 2H, J 9.5, 3.5 Hz, phthalazine‐H); 13 C NMR (125 MHz, DMSO‐ d 6 ) δ C (ppm): 20.5 (CH 3 ), 115.1, 125.3, 128, 129.3, 129.8, 132.1, 133.5, 139.6, 149.9, 155.7, 158.8 (C═O), 159 (C═O); MS m/z (%): 346 [M‐15] + (2%), 217 (100%); Anal . Calcd for C 18 H 15 N 7 O 2 (361.37): C, 59.83; H, 4.18; N, 27.13, Found: C, 59.71; H, 4.05; N, 26.98%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beam et al [85] have reported a novel synthesis of 5-aminopyrazoles 155 from polylithiated C (α), N -thiosemicarbazones (X = S) or C (α), N -semicarbazones (X = O). The polylithiated intermediates, prepared from C (α), N -thiosemicarbazones (X = S) or C (α), N -semicarbazones (X = O) 154 and an excess of lithium diisopropylamide (LDA), underwent cyclization and on subsequent hydrolysis gave the 5-aminopyrazole derivatives 155 (Scheme 43).…”
Section: Reviewmentioning
confidence: 99%
“…β-Oxo nitriles are prepared in turn by reaction of halo ketones with sodium or potassium cyanide. Other known methods for the preparation of aminopyrazoles are based on intramolecular cyclization of acetophenone thiosemicarbazones [6] and semicarbazones [7,8], reaction of β-amino-β-arylacrylonitrile [9] or α,β-dichloropropionitrile [10] with hydrazines, and decarboxylation of 5-amino-3-arylpyrazole-1-carboxylic acids [3]. Hartmann and Liebscher [5] proposed a procedure for the synthesis of aminopyrazoles via reaction of hydrazine with β-aryl-β-chloroacrylonitriles.…”
mentioning
confidence: 99%